2003
DOI: 10.1046/j.1365-3083.2003.01232.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Soluble Cytotoxic T‐Lymphocyte‐Associated Antigen‐4 Molecule in Patients with Systemic Lupus Erythematosus

Abstract: A soluble form of cytotoxic T-lymphocyte-associated antigen-4 (sCTLA-4) was recently found and shown to possess a downregulatory function as a membranebound CTLA-4 molecule. The purpose of the study was to investigate the expression of sCTLA-4 molecule in patients with systemic lupus erythematosus (SLE). One hundred patients with SLE and 40 age-and sex-matched healthy individuals were enrolled in the study. The results showed that patients with SLE have significantly higher levels of sCTLA-4 in sera than healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 14 publications
8
80
3
Order By: Relevance
“…In addition, mutations in the amino acid sequence of the cytoplasmic tail of CTLA-4 can lead to its accumulation at the cell surface [50] although genetic studies have not indicated that mutations at this site predisposes to SLE. A soluble form of CLTA-4 has also been described, which is predominantly expressed on resting T-cells [51] and is increased in the serum of patients with SLE [52,53]. The soluble form of CLTA-4 lacks the transmembrane domain of the CTLA-4 gene implying that alterations in its expression are not secondary to changes in the recycling of membrane CTLA-4.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mutations in the amino acid sequence of the cytoplasmic tail of CTLA-4 can lead to its accumulation at the cell surface [50] although genetic studies have not indicated that mutations at this site predisposes to SLE. A soluble form of CLTA-4 has also been described, which is predominantly expressed on resting T-cells [51] and is increased in the serum of patients with SLE [52,53]. The soluble form of CLTA-4 lacks the transmembrane domain of the CTLA-4 gene implying that alterations in its expression are not secondary to changes in the recycling of membrane CTLA-4.…”
Section: Discussionmentioning
confidence: 99%
“…A sCTLA-4, namely a functional molecule with specific CD80 and CD86 binding ability, generated by alternatively spliced mRNA has been described [10,13,20,[49][50][51][52][53]. The mRNA encoding sCTLA-4 consists of three exons: exon 1 encoding the leader peptide, exon 2 the ligand-binding domain, and exon 4 the cytoplasmic tail, but it lacks exon 3 encoding the transmembrane domain [10,20,53].…”
Section: Soluble Form Of Ctla-4mentioning
confidence: 99%
“…The mRNA encoding sCTLA-4 consists of three exons: exon 1 encoding the leader peptide, exon 2 the ligand-binding domain, and exon 4 the cytoplasmic tail, but it lacks exon 3 encoding the transmembrane domain [10,20,53]. The spliced transcript produces a 23-kDa sCTLA-4 characterized by a cytoplasmic tail shorter than that of the full-length form of the CTLA-4 antigen.…”
Section: Soluble Form Of Ctla-4mentioning
confidence: 99%
See 2 more Smart Citations